Overcome social anxiety disorder and develop visionary leadership in uncertain environments: The important role of psychological resilience - Guan, Yi; Wang, Yao; Zhang, Jiaojiao; Cao, Yuan (Frontiers in Psychology, 2023)
Uncertainty is the main feature of business environment in the post-COVID-19 era. People who taking management positions in uncertain environment constantly encounter with unprecedented risks and challenges. Many of them are difficult to adapt to such environment, and thus experience sever anxiety or even burnout, showing the symptoms of Social anxiety disorder (SAD), failing to exert effective leadership in social interaction contexts. How can managers overcome Social anxiety disorder (SAD) and effectively motivate their subordinates in uncertain environment? This study explored the important role of psychological resilience. Using sample data collected from 82 leaders and 363 subordinates of 8 enterprises in China from May to June 2020, the current study reveals that a high degree of psychological resilience enables managers to maintain intrinsic motivated at work in uncertain environment, which further cause the managers to perform better in identifying the organizations’ vision and displaying visionary leadership than those who with a low degree of psychological resilience. The current study enriches the knowledge of manager’s psychological well-being and effective leadership in post-COVID-19 era.